The Emergence of Theileria parva in Jonglei State, South Sudan: Confirmation using molecular and serological diagnostic tools - Marcellino, Wani L.; Salih, Diaeldin A.; Njahira, Moses N.; Ndiwa, Nicholas N.; Araba, A.; El Hussein, A.M.; Seitzer, U.; Ahmed, J.S.; Bishop, Richard P.; Skilton, Robert A. (Hindawi Limited, 2017)
A cross-sectional survey was carried out in four counties of Jonglei State, South Sudan, between May and June 2012 to determine the distribution and northern limit of Theileria parva, the causative agent of East Coast fever in cattle, and its tick vector Rhipicephalus appendiculatus, as a prerequisite to the deployment of relevant control strategies. A total of 1636 ticks, 386 serum samples and 399 blood samples were collected from indigenous, apparently healthy, cattle of different age groups. Tick species were identified morphologically, and the identity of R. appendiculatus was confirmed by DNA barcoding. Overall, the T. parva infection rate in R. appendiculatus was 25% as shown by nested PCR. ELISA was used to assess antibodies to T. parva, and the overall seroprevalence was 22.8%. PCR of the blood samples showed 55 (13.8%) were positive for T. parva. This is the first molecular confirmation of T. parva DNA in areas north of Juba, where it was previously known and established. The northern limit of T. parva was determined as N⁰06.17.792, about 242 Km north from Juba. Implication of this limit on the epidemiology and control of ECF is discussed.